ENERGY expenditure of COmmuting to school (ENERGYCO): protocol for a cluster randomized controlled trial - Campos-Garzón, Pablo; Valle-Muñoz, Víctor Manuel; Segura-Díaz, José Manuel; Ávila-García, Manuel; Saucedo-Araujo, Romina Gisele; Ruiz-Alarcón, Ana; López-Centeno, Francisco David; Pérez De Arrilucea Le Floc’h, Unai A.; Alcantara, Juan M. A.; Medel-Carbonell, Luis Miguel; Rodriguez-Sanchez, David; Ramírez-Osuna, Ana; et al. (Frontiers in Public Health, 2025)
IntroductionThis article outlines the rationale and methodology of the ENERGY expenditure of COmmuting to school study (the ENERGYCO study), a cluster-randomized controlled trial. The ENERGYCO study is divided into two phases: Phase I will aim; to assess the physical activity energy expenditure (PAEE) of different modes of commuting to school (i.e., walking, cycling, and motorized-vehicle) using indirect calorimetry in Spanish adolescents; and Phase II will aim to assess the effect of a school-based cycling intervention on resting metabolic rate and PAEE, as well as on other physiological, physical, and psychosocial outcomes on Spanish adolescents.MethodFor Phase I, a convenience sample of ~50 adolescents will be recruited. These participants will have their PAEE assessed in three different modes of commuting. Regarding phase II, a total of 300 adolescents from different schools in three Spanish cities will participate in this cluster randomized controlled trial. As many schools as necessary to meet the target sample will be included. In addition, each school will be randomized as either an intervention or control group. Participants from intervention schools will be asked to complete a school-based cycling intervention, while participants from control schools will be asked to continue their same habits for 8 weeks. The school-based cycling intervention will last for 8 weeks and will include Bikeability sessions, along with encouragement strategies to increase adherence to cycling to and from school.ConclusionThe ENERGYCO study will provide novel insights into the PAEE associated with different modes of commuting to school using indirect calorimetry, as well as a comprehensive overview of how an 8-week school-based cycling intervention impacts resting energy expenditure, daily energy expenditure, and the physical and psychosocial health of adolescents.